KUALITAS UDANG YANG DIJUAL DI PASAR JAKARTA SELATAN DARI ASPEK MIKROBIOLOGI - Harsojo Harsojo (The East Java Biological Society, 2008)
This study was to know the quality of shrimp sold at some market in south Jakarta. Parameters measured were total amount of aerobic bacteria, total amount of coliform, Escherichia coli, Staphylococcus, Salmonella and pH. Result of the research shows that no Salmonella detected in all samples observed. However, the amount of aerobic bacteria were found in the range from 81.0 × 10² to 59.0 × 105 cfu/g, while coliform bacteria from 20.0 × 10² to 79.0 × 10³ cfu/g. Total amount of E. coli found in the range 0 to 26.0 ×10³ cfu/g, while Staphylococcus bacteria were found in the range 0 to 26.0 × 104 cfu/g. The pH of shrimp samples were found in the range from 6.60 to 7.24. The total shrimp samples have exceeded allowable limit according to Indonesian National Standard were 85.7%.